Dinamika Determinan Parental: Studi Kualitatif Pola Asuh Orang Tua pada Perokok Balita di Indonesia - Ulfa, Annisa Sayyidatul; Damayanti, Rita (UI Scholars Hub, 2023)
Background. Indonesia is ranked third in the world for the highest number of smokers after China and India. An increase in the prevalence of child smokers occurred in 2018 from 7.2% to 9.1%, particularly the phenomenon of smoking was also found. The emergence of this phenomenon indicates the neglect of parenting practices carried out by parents towards toddlers who smoke. This is because smoking has positive social acceptance and is considered a common habit in Indonesian society. Aim. To analyze dynamics of parenting and role of social environment of parents who neglect toddlers, causing toddlers to become smokers. Method. This is qualitative research with case study design, conducted in South Sumatra, West Java and East Java in November 2021-January 2022. Result. Parents estimate that the environmental conditions of the majority of smokers are the beginning of toddlers smoking. Parenting role is fully given to the mother, resulting double burden which makes the mother's inability to care for toddlers. Neglection causes the incidence of toddler smoking, the social environment also supports smoking and its normalization, so efforts are needed to improve toddlers' care